EFFECT OF MESSAGE IN HEALTH COMMUNICATION: THE CASE OF VACCINE CAMPAIGN 'MR' 'MINISTRY OF HEALTH REPUBLIC OF INDONESIA - ANDHIKA KURNIAWAN PONTOH; FARRAH MARDIATI SOEHARNO; MUTIA ADIA RISIAD (CV KULTURA DIGITAL MEDIA, 2020)
Public health campaign messages are intended to influence public attitudes and behavioral beliefs about health consequences. The operational formula for creating persuasive messages is health vulnerability multiplied by severity, using a loss framework to motivate the public to change behavior for healthy living. This paper intends to analyze the persuasive message of the MR vaccine campaign and see the response that occurred in the community to the health campaign. This paper attempts to examine the process of community social assessment that results in a response of rejection and a boomerang effect on campaign messages. This paper concludes that the negative boomerang effect on the MR Vaccine campaign carried out by the Indonesian Ministry of Health is largely due to the ego involvement of key figures or opinion leaders that influence the perceptions and behavior of the audience receiving the message. Opinion leaders in this case are religious institutions such as MUI which publishes findings on the content of MR vaccine. The boomerang effect that occurs is the contrasting attitudes and behaviors of the audience of campaign message recipients who have anchor positions / principles that are opposite and far from the contents of the MR Vaccine campaign message.